Overcoming water scarcity and quality constraints: Water and Rural Livelihoods - Vincent, Linden (International Food Policy Research Institute, 2001)
Livelihoods are the means people use to support themselves, to survive, and to prosper. Livelihoods are an outcome of how and why people organize to transform the environment to meet their needs through technology, labor, power, knowledge, and social relations.